Coronal alignment in total knee arthroplasty and its effect on functional outcome: A retrospective study - Maharjan, Promish; Chen, Wang; Dong, Guo Yu; Zheng, Wang Shang (Grande Medical Journal, 2024)
Background This retrospective study was conducted to compare the coronal alignment of the lower extremity before and after surgery in patients undergoing total knee replacement by assessing the mechanical axis in the full-length weight-bearing radiograph taken preoperatively and post-operatively, and to assess the clinical outcome after TKA with reference to the mechanical axis. Method Fifty eight patients who underwent primary TKA from date October 2013 to March 2017 were included in the study. The patient’s demographics such as age, gender primary TKA were noted. All patients underwent clinical and radiological evaluation, including standardized radiographs (anterior-posterior long-leg X-ray). For clinical outcome scoring the Hospital for Special Surgery score (HSS) and Western Ontario and McMaster Universities Arthritis Index (WOMAC) were used. One-way ANOVA was used to compare the outcome of the surgery and the alignment (p <0.05). Result Out of the 58 patients included in the study, 16 (27.58%) were male and 42 (72.41%) were female with age ranged between 34 to 88 years (mean 65.44 years). The male patient’s age ranged from 53 to 85 (median 63 years) and that of female patients ranged from 52 to 83 (median 65.5 years). The overall mean HSS score improved from 59.86 ± 10.91 preoperatively to 82.52 ± 11.04 in one year postoperatively (<0.0001) and WOMAC score improved from 33.98 ± 11.25 to 10.4 ± 6.06 (P<0.0001) after 1 year from the TKA respectively. Both showed a significant difference in the results. There were 50 patients with pre-operative Varus alignment and 8 with pre-operative valgus alignment. Pre-operative Varus groups have a post-operative HSS score of83.98±9.962153 and that of pre-operative valgus groups has HSS score of 77.625±14.20199. Similarly, pre-operative Varus group had a postoperative WOMAC score of 9.38±5.27949 and that of the valgus group had 12±9.273618. In these two groups, there was no significant difference between their post-operative HSS score (P=0.2571) and WOMAC score (P=0.4590). After the surgery, 25 patients (43.10%) had varus alignment, 22 patients (37.9%) had neutral alignment and 11 patients (18.97%) had valgus alignment. The post-operative mechanical axis group was divided into the post-op varus group, post op neutral group, and post-op valgus group. After comparing within the groups, the neutral group had the highest HSS score (91.3636±4.1946, lowest WOMAC score (5.2272±1.37945), P<0.005, which showed the best result and the HSS score of post-operative varus group was (82.12±7.5), the WOMAC score was (9.64±4.344) showing the moderate result. The postoperative valgus group has HSS score (68.82 + 9.39), WOMAC score (16.3636 + 8.205), showing worst result. Conclusion Total Knee Arthroplasty is a good treatment modality for primary osteoarthritis. The coronal alignment before surgery has no significant effect on the function after total knee arthroplasty. However, the post-operative coronal alignment of the lower limbs was related to the clinical function of the patients. The outcome of the patient with the mechanical axis was the best with neutral groups followed by the Varus group and was the worst in the valgus group.